Pengaruh Pemberian Fraksi n-Heksan Ekstrak Etanol Daun Kelor (Moringa oleifera L.) Terhadap Kadar Low-Density Lipoprotein (LDL) Tikus Jantan Galur Sprague dawley : Efek Antikolestrol Fraksi n-Heksan Ekstrak Etanol Daun Kelor (Moringa oleifera L.) - Kusumawardani, Nurul; Fauzi, Rizal; Emelda, Emelda; Estiningsih, Daru; Sukma Ananda , RA Dewinta; Nabila , Lathifa (Brawijaya University, 2024)
This study aimed to determine the effect of the n-hexane fraction of Moringa leaf ethanol extract (Moringa oleifera L.) on low-density lipoprotein (LDL) levels in Sprague Dawley male rat strains fed a high-fat diet. This study used a pre-test and post-test control design on male rats of the Sprague Dawley strain. Thirty-six male white rats of the Sprague Dawley strain were given high-fat diet and then divided into six groups: group I was normal group, group II negative control was given CMC Na, Group III positive control was given Simvastatin 10 mg, Group IV, V, VI was given n-hexane fraction of ethanol extract of Moringa leaves (Dose 3,722 mg/kgBW; 7.444 mg/kgBW; 14,888 mg/kgBW). The results of measuring low-density lipoprotein (LDL) levels in animals were measured after 14 days of research as a post-test. Based on statistical analysis, there was no significant difference between the positive control group and the three treatment groups (p=1,000). The results of this study can conclude that the dose of the n-hexane fraction of Moringa leaves has a significant effect on decreasing LDL levels in male Sprague Dawley rats with the best % reduction at a dose of 14.89 mg/kg BW (61.17%), with a linear regression equation y=-0.0408x + 1.079; (R2=0.986). The results of this study indicate that the n-hexane part of Moringa leaves may reduce low-density lipoprotein levels in male white Wistar rats induced by high-fat.